PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) BERBANTU AUDIO VISUAL TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS X SMAN 3 PEKANBARU - Rahmat Ramadansur; Marta Dinata; Annisa Nur Rahmadhani Al-Khani (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This study aims to determine the effect of the group investigation cooperative learning model assisted by audio visual aids on the motivation and learning outcomes of class X SMAN 3 Pekanbaru. This research was conducted in class X of SMAN 3 Pekanbaru in the 2022/2023 Academic Year. The research design used was quasi-experimental, using the matching only pretest posttest control design. The research sample was class X students with 36 experimental and 36 control classes respectively taken by Simple Random Sampling. Data collection was carried out through pretest, posttest and observation sheets. Based on the research results obtained for the learning motivation questionnaire value in the control class was 2.48 with a percentage value of 62.10% in the medium category, while for the learning motivation questionnaire value in the experimental class given the treatment of cooperative learning model group investigation type of 2,97 with a percentage value of 74.47% in the high category. Based on these categories, there was an increase in learning motivation in the experimental class which was given treatment with the group investigation type cooperative learning model assisted by audio-visual aids. For the mean N-Gain in the control class 0.29 (low), while in the experimental class 0.52 (moderate). On the results of the N-Gain t-test the value of Sig. (2-tailed) Equal variances not assumed on the output of the Independent sample test value is 0.000 <0.05 then reject Ho which means that there is a significant difference between the N-Gain control class which is given treatment with conventional learning and the experimental class which is given treatment with cooperative learning model with the type of group investigation assisted by audio visual which shows an increase in learning outcomes. Thus learning using the cooperative learning model type group investigation assisted by audio visual aids in virus material affects the motivation and learning outcomes of class X SMAN 3 Pekanbaru in the 2022/2023 Academic Year.